Moving to the cloud: Estimating the internet connection bandwidth - Silva, L. F. da. (2011)
IT Infrastructures (ITIs) have long been understood in terms of people and resources such as servers, routers, firewalls and operating systems, among other components, running and providing services inside the organization. The need to reduce the cost of ITI ownership, by offloading its capacity to third parties, has motivated organizations to consider the Cloud Computing alternative. The main drawback they face when opting for the cloud is the dependency on and requirements of the internet connection, since it must be fast and reliable. This paper addresses this concern by providing guidelines for estimating internet connection bandwidth requirements for a prototypical cloud-based organization represented by means of an IT infrastructure pattern. ITI patterns are reusable and proven solutions to support the ITI design process and to facilitate the communication among stakeholders.